9
$\begingroup$

Find the specialized solution of $H''(r)-aH'(r)=0$ that satisfies $H'(0) = \frac{1}{p^2}$ and $H(0) = \frac{H'(0)}{a}(1+\frac{N}{Y}e^w)$

The question:

  1. Solve the above mathematic question
  2. Rewrite your solution to 1 in an appropriate form
  3. (Optional) This might be a hint (to some extents)

    Speak your answer to task 2 out loud!


Disclaimer: I am not the original author of this puzzle. It was an image that showed up in an instant messaging group. The original image contains solution for 1 and 2 and is written in my native language - Simplified Chinese.

$\endgroup$
8
$\begingroup$

This looks like:

Happy New Year

Update:

Here's my solution:

enter image description here

$\endgroup$
4
$\begingroup$

Part 1:

Start from $H''(r)-aH'(r)=0$ and let $G(r) = H'(r)$, so $G'(r)-aG(r)=0$. The general solution for this linear equation is $G(r) = be^{ar}$ ($b$ constant). Now $\frac{1}{p^2} = H'(0) = G(0) = b$. Integrating $G(r)$ gives $H(r) = \frac{e^{ar}}{a p^2}+C$ ($C$ constant). $H(0) = \frac{1}{a p^2} + C$, so

$$\frac{1}{a p^2} + C = \frac{H'(0)}{a}(1+\frac{N}{Y}e^w) = \frac{1}{a p^2}+\frac{Ne^w}{a p^2 Y}$$

so $C = \frac{Ne^w}{a p^2 Y}$ and

$$H = \frac{e^{ar}}{a p^2}+\frac{Ne^w}{a p^2 Y}$$

Part 2:

Rewriting this becomes

$$H=\frac{Ne^w}{a p p Y} + \frac{Y e^{ar}}{a p p Y}$$

and finally

$$H a p p Y = N e^w + Y e^{a r}$$

or, as @pirate correctly guessed,

Happy New Year

$\endgroup$
  • $\begingroup$ G(rrr) = bear is also a nice stylistic choice of variables. $\endgroup$ – svavil Jan 2 at 8:30

Your Answer

By clicking "Post Your Answer", you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.